1994
DOI: 10.1007/bf02049815
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and sexual and gynecologic function after heal pouch-anal anastomosis

Abstract: Although childbirth appears safe, gynecologic problems, such as dyspareunia and formation of pelvic cysts, may be underestimated after IPAA. The effects of IPAA on fertility are still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 18 publications
5
58
0
Order By: Relevance
“…A total of 141 females were pregnant after the chronic ulcerative colitis diagnosis, but before ileal pouch-anal anastomosis (236 pregnancies; mean, 1.7) and 87 percent delivered vaginally. A mean of five (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] years after ileal pouch-anal anastomosis, 135 females were pregnant (232 pregnancies; mean, 1.7). Comparison of pregnancy and delivery before and after ileal pouch-anal anastomosis in the same females (n = 37) showed no difference in birth weight, duration of labor, pregnancy/ delivery complications, vaginal delivery rates (59 percent before vs. 54 percent after ileal pouch-anal anastomosis), and unplanned cesarean section (19 vs.14 percent).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 141 females were pregnant after the chronic ulcerative colitis diagnosis, but before ileal pouch-anal anastomosis (236 pregnancies; mean, 1.7) and 87 percent delivered vaginally. A mean of five (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] years after ileal pouch-anal anastomosis, 135 females were pregnant (232 pregnancies; mean, 1.7). Comparison of pregnancy and delivery before and after ileal pouch-anal anastomosis in the same females (n = 37) showed no difference in birth weight, duration of labor, pregnancy/ delivery complications, vaginal delivery rates (59 percent before vs. 54 percent after ileal pouch-anal anastomosis), and unplanned cesarean section (19 vs.14 percent).…”
mentioning
confidence: 99%
“…Previous reports from this institution and others have documented that patients after IPAA can carry their pregnancies to term with minimal alterations in pouch function. [1][2][3][4][5][6] However, the most controversial aspects of IPAA and pregnancy relate to the preferred route of delivery (vaginal or cesarean section) and the longterm effects of delivery on pouch function. Most studies have been limited by small numbers of patients and short follow-up.…”
mentioning
confidence: 99%
“…The decision of performing cesarean section in pregnant women with IBD is still a matter of debate (8,40). Some studies have demonstrated that the rates of incontinence and sphincter tear were lower in patients who underwent caesarean section, compared to those who preferred vaginal delivery, suggesting that caesarean section was the best delivery method in women with IBD (41,42). In another study, it was demonstrated that the anal sphincter tear which occurred during vaginal delivery did not affect continence, and reported that vaginal delivery reduced surgical procedure and adhesion formation in the high risk patient group (43).…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of transient dysfunction of the gynecological or reproductive organs after IPAA, [13][14][15] especially maturation disorder of the ovaries and obstruction of the fallopian tubes. According to Koganei et al,5 fertility should not be affected by IPAA.…”
Section: Discussionmentioning
confidence: 99%